Evolving technology: the TRIFLO tri-leaflet mechanical valve without oral anticoagulation: a potential major innovation in valve surgery - Carrel, Thierry; Vogt, Paul R.; Obrist, Dominique; Schaff, Hartzell (Frontiers in Cardiovascular Medicine, 2023)
The aortic valve is the most frequently diseased valve and aortic stenosis (AS) is the most prevalent valvular heart disease in developed countries. The diseased native aortic valve can be replaced by either a biological or mechanical valve prosthesis. The main concerns relate to durability, the need for oral anticoagulants and the incidence of complications related to this medication. Experimental, computational and biomolecular blood flow studies have demonstrated that the systolic forward flow but also the reverse flow phase at the end of the systole and leakage during the diastolic phase is mainly responsible for platelet activation and thrombosis. Better design of mechanical prosthetic heart valves must ensure smooth closing during flow deceleration and must eliminate high-shear hinge flow during diastole to prevent life-threatening thrombosis. A novel tri-leaflet valve should combine the favorable hemodynamics and the durability of existing mechanical heart valves and eliminate the less favorable characteristics, including the extremely rapid closing. In this paper, we discuss some issues of current mechanical heart valve prostheses and present a new valve design with the potential for significant innovation in the field. The TRIFLO Heart Valve, is a rigid, three-leaflet central flow heart valve prosthesis consisting of an alloyed titanium housing, and three rigid polymer (PEEK) cusps. This valve has a physiological operating mode. During the forward flow phase, the intraventricular pressure opens the leaflets so that blood can freely flow through with little obstruction, and with the deceleration of the blood flow, the leaflets close early and smoothly, minimizing blood flow regurgitation, blood cell damage, and activation of the coagulation cascade. Pre-clinical studies have shown pretty favorable results and a first-in-man study should start very soon.